Metabolic Syndrome in Estonia: Prevalence and Associations with Insulin Resistance - Triin Eglit; Tarvo Rajasalu; Margus Lember (International Journal of Endocrinology)
Recently, it has been suggested that metabolic syndrome should be considered a premorbid condition in younger individuals. We evaluated the prevalence of metabolic syndrome in Estonia and compared the characteristic profiles between morbid metabolic syndrome (previously established diabetes, hypertension, or dyslipidaemia) and premorbid metabolic syndrome subgroups. Our study was a cross-sectional, population-based sample of the general population in Estonia aged 20–74 years (n=495). Metabolic syndrome was diagnosed by National Cholesterol Education Program Adult Treatment Panel III criteria. Insulin resistance was estimated using the homeostasis model assessment (HOMA-IR). The crude and weighted prevalence of metabolic syndrome was 27.9% and 25.9%, respectively. Despite being significantly younger, the premorbid subgroup showed similar levels of insulin resistance as the morbid subgroup (mean HOMA-IR ± SD 2.73±1.8 versus 2.97±2.1, P=0.5). The most important attribute of metabolic syndrome is insulin resistance, which already characterises metabolic syndrome in the early stages of its metabolic abnormalities.